Associations of changes in diet and leisure-time physical activity with employer's direct cost of short-term sickness absence. Issue 2 (7th February 2020) - Salmela, Jatta; Lahti, Jouni; Mauramo, Elina; Pietiläinen, Olli; Rahkonen, Ossi; Kanerva, Noora
Abstract: Several unhealthy lifestyles are associated with increased sickness absence (SA). This study examined the associations of changes in diet and leisure-time physical activity (LTPA) with employer's direct cost of subsequent short-term (<10 working days) SA. The survey data from phases 1 (2000−2002) and 2 (2007) of the Helsinki Health Study (HHS), a longitudinal cohort study of initially 40−60-year-old employees of the City of Helsinki, Finland, were linked with SA register data. Final data consisted of 4157 employees. Dietary habits were inquired with a short food frequency questionnaire. Consumption of fruits (F) and vegetables (V) was used to indicate healthiness of diet. LTPA was measured with a series of questions on the intensity and the amount of LTPA. Data on short-term SA and salaries (2008−2012) were received from the employers' registers. A two-part model was used to analyse the associations. Those who improved their F&V consumption from non-daily to daily and persevered physically active got 620 € (95% CI −1194, −47) lower cost than those remaining non-daily F&V consumers and physically inactive. When examining LTPA only, those who persevered physically active or improved from moderately active to active got 19% less cost for the employer than those remaining inactive. Dietary changes were not independently associated with the cost. Improving employees' diet and LTPA may reduce employer's direct cost of SA. Although the associations of diet with SA cost were not statistically significant, improvements in diet may contribute to the beneficial associations of LTPA and employer's cost of SA.